Theosophy across boundaries: transcultural and interdisciplinary perspectives on a modern esoteric movement - Krämer, Hans Martin; Strube, Julian (SUNY Press, 2020)
"Demonstrates that Theosophy was part of a truly global movement and played an important role in the general histories of religion, science, philosophy, art, and politics"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Interdisziplinäre Forschung; Religionswissenschaft; Einfluss; Esoterik; Theosophie